2021
DOI: 10.1073/pnas.2100680118
|View full text |Cite
|
Sign up to set email alerts
|

Copper binding by a unique family of metalloproteins is dependent on kynurenine formation

Abstract: Some methane-oxidizing bacteria use the ribosomally synthesized, posttranslationally modified natural product methanobactin (Mbn) to acquire copper for their primary metabolic enzyme, particulate methane monooxygenase. The operons encoding the machinery to biosynthesize and transport Mbns typically include genes for two proteins, MbnH and MbnP, which are also found as a pair in other genomic contexts related to copper homeostasis. While the MbnH protein, a member of the bacterial diheme cytochrome c peroxidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 73 publications
(114 reference statements)
0
14
0
Order By: Relevance
“…Other genes frequently found in operons with bp2923 homologs code for putative proteins involved in Cu transport, binding, or homeostasis, including the copper chaperones ScoC and Pcu A C that participate in the assembly of heme-copper subunits of respiratory complexes ( 39 , 40 ), and the Cu-binding proteins YcnI and CopC ( 41 , 42 ). These operons also comprise MbnPH-like genes notably found in biosynthesis operons of copper-binding methanobactin-type molecules ( 43 , 44 ) and AhpC_TSA genes, whose products detoxify peroxides ( 45 ). Long intergenic distances between bp2923 homologs and the following genes are generally observed, indicating a potential role in regulation.…”
Section: Resultsmentioning
confidence: 99%
“…Other genes frequently found in operons with bp2923 homologs code for putative proteins involved in Cu transport, binding, or homeostasis, including the copper chaperones ScoC and Pcu A C that participate in the assembly of heme-copper subunits of respiratory complexes ( 39 , 40 ), and the Cu-binding proteins YcnI and CopC ( 41 , 42 ). These operons also comprise MbnPH-like genes notably found in biosynthesis operons of copper-binding methanobactin-type molecules ( 43 , 44 ) and AhpC_TSA genes, whose products detoxify peroxides ( 45 ). Long intergenic distances between bp2923 homologs and the following genes are generally observed, indicating a potential role in regulation.…”
Section: Resultsmentioning
confidence: 99%
“…Other genes frequently found in operons with bp2923 homologues code for proteins involved in Cu transport, binding or homeostasis, including the chaperones ScoC and Pcu A C that participate in the assembly of heme-copper subunits of respiratory complexes (Serventi et al, 2012, Trasnea et al, 2016), and the Cu-binding proteins YcnI and CopC (Damle et al, 2021, Lawton et al, 2016). Some of these operons also comprise MbnPH-like genes notably found in biosynthetic operons of Cu-binding methanobactin-type molecules (Kenney and Rosenzweig, 2018, Manesis et al, 2021), and AhpC_TSA genes, whose products detoxify peroxides (Dubbs and Mongkolsuk, 2007). Long intergenic distances between cruR homologues and the following genes are generally observed.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the predicted ET rate for the hopping mechanism is again ∼10 6 times that for the single step tunneling reaction, suggesting that electron hopping is dominant in the MbnPH complex. Previous studies have shown that replacement of Trp176 with tyrosine does not affect the modification of Trp174, 23 suggesting that tyrosine can also support this electron/hole hopping pathway. Thus, MbnH uses tryptophan residues as hopping stations both between its two hemes and between heme 1 and the target of modification, Trp 174, in its substrate, MbnP.…”
Section: Decay Of the High-valent Intermediate In Mbnhmentioning
confidence: 92%
“…The predicted pathway for oxidation includes MbnP Trp 176, a strictly conserved residue (Figure S18). 23 For a multistep hopping pathway, H AB for the first segment from Trp 174 to Trp 176 has a calculated value of 7.8 × 10 −4 with a β of 0.9 Å −1 . The second segment from Trp 176 to heme 1 has a calculated H AB of 1.9 × 10 −5 and a β of 1.24 Å −1 .…”
Section: Decay Of the High-valent Intermediate In Mbnhmentioning
confidence: 99%
See 1 more Smart Citation